IMPLEMENTATION OFF MOSQUE MANAGEMENT BASED ON RELIGIOUS TOURISM AT THE SUNGAI BANAR MOSQUE SOUTH KALIMANTAN - Safitri, Rizkia Najmi; Falikhah, Nur; Herlita, Jumi (Program Studi Manajemen Dakwah - Fakultas Dakwah dan Ilmu Komunikasi - UIN Syarif Hidayatullah Jakarta, 2024)
Religious tourism is a trip to worship, pray, or do certain ceremonies (rituals). The mosque is one of the choices for the community in meeting their spiritual needs or religious tour. There is no exception to the Sungai Banar Jami’ Mosque, located in South Amuntai, Hulu Sungai Utara Regency. The oldest mosque has an essential history for people. The upstream of the Sungai Banar Jami’ Mosque is one of the spiritual tourism destinations, so the Sungai Banar Jami’ Mosque needs to apply management functions, including planning, organizing, actuating, and evaluating. This is a field research with data collection methods: observation, interviews, and documentation. The results showed that the Sungai Banar Jami’ Mosque management had implemented a management function, namely planning, by setting goals divided into short, medium, and long-term plans. Organizing includes the formation of management structures, division of tasks, and good communication. Actuating includes giving orders, direction, and motivation. Evaluating includes the beginning, middle, and end.